2005
DOI: 10.1002/chem.200500758
|View full text |Cite
|
Sign up to set email alerts
|

(S)‐Selective Kinetic Resolution and Chemoenzymatic Dynamic Kinetic Resolution of Secondary Alcohols

Abstract: (S)-Selective kinetic resolution was achieved through the use of a commercially available protease, which was activated with a combination of two different surfactants. The kinetic resolution (KR) process was optimized with respect to activation of the protease and to the acyl donor. The KR proved to be compatible with a range of functionalized sec-alcohols, giving good to high enantiomeric ratio values (up to >200). The enzymatic resolution was combined with a ruthenium-catalyzed racemization to give an (S)-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(49 citation statements)
references
References 71 publications
0
49
0
Order By: Relevance
“…The synthesis of (S)-esters was performed with a combination of 6a and subtilisin treated with surfactants. [22] Bäckvall and coworkers have recently demonstrated a large-scale DKR.…”
Section: Racemization Catalysts and Reaction Conditions For Dkr Of Almentioning
confidence: 98%
“…The synthesis of (S)-esters was performed with a combination of 6a and subtilisin treated with surfactants. [22] Bäckvall and coworkers have recently demonstrated a large-scale DKR.…”
Section: Racemization Catalysts and Reaction Conditions For Dkr Of Almentioning
confidence: 98%
“…Since the first observation by Lippert et al, [1] the phenomenon of dual fluorescence for 4-(N,N-dimethylamino)benzonitrile (DMABN), one of the donor-acceptor p-conjugated (D-p-A) compounds, has led to numerous theoretical and experimental studies to explore the origin of intramolecular charge-transfer (ICT) fluorescence, [2][3][4] which plays a key Abstract: Experimental and theoretical methods were used to study newly synthesized thiophene-p-conjugated donor-acceptor compounds, which were found to exhibit efficient intramolecular charge-transfer emission in polar solvents with relatively large Stokes shifts and strong solvatochromism. To gain insight into the solvatochromic behavior of these compounds, the dependence of the spectra on solvent polarity was studied on the basis of Lippert-Mataga models.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral Cr(salen)F 2 is readily available as either the ( R,R )- or ( S,S )-enantiomer, and careful selection of commercially available enzymes allows for enrichment of either stereoisomer of the product. 16 To demonstrate this, we used Pd(II)/bis-sulfoxide 1 /( S,S )- 2 and resolution with the commercially available protease Subtilisin Carlsberg to generate (+)-3 in 99%ee and nearly identical overall yield to the route previously described for (−)-3 (Scheme 2, 3). This matches the flexibility of other catalyst-controlled approaches to these compounds, like the SAE which was utilized to make (+)-3 in a total synthesis of the potent biotoxin Azaspiracid A.…”
Section: Resultsmentioning
confidence: 99%